2005
DOI: 10.1002/jrs.1386
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra of CN vibrations of acetonitrile in aqueous and other solutions. Experimental results andab initio calculations

Abstract: Quantum-chemical calculations showed a possibility of formation of dimers in pure acetonitrile, as well as molecular aggregates in its solutions with water and formic acid. Accordingly, a low-wavenumber asymmetry of the C N band in Raman spectra of liquid acetonitrile can be related to presence of dimers. In neutral solvents within the range of concentrations 1-0.1 mole fraction, the asymmetry of the C N band is preserved. However, in aqueous solutions and solutions with formic acid, an asymmetry of another ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 10 publications
2
29
0
Order By: Relevance
“…Studying the CN triple bond vibration of acetonitrile in aqueous and other solutions, Tukhvatullin et al 255 were able to show by quantum chemical calculations that there is a possibility of dimer formation and unlike molecule aggregates in these solutions. Studying the CN triple bond vibration of acetonitrile in aqueous and other solutions, Tukhvatullin et al 255 were able to show by quantum chemical calculations that there is a possibility of dimer formation and unlike molecule aggregates in these solutions.…”
Section: Studies In Binary Mixturesmentioning
confidence: 99%
“…Studying the CN triple bond vibration of acetonitrile in aqueous and other solutions, Tukhvatullin et al 255 were able to show by quantum chemical calculations that there is a possibility of dimer formation and unlike molecule aggregates in these solutions. Studying the CN triple bond vibration of acetonitrile in aqueous and other solutions, Tukhvatullin et al 255 were able to show by quantum chemical calculations that there is a possibility of dimer formation and unlike molecule aggregates in these solutions.…”
Section: Studies In Binary Mixturesmentioning
confidence: 99%
“…1(d)). 13,14 The dipole moment of such an aggregate is 5.05 D, which is higher than the additive sum of the dipole moments of interacting molecules. Accordingly, aggregates propan-2-ol-acetonitrile are formed and should exist for a long time.…”
Section: Resultsmentioning
confidence: 99%
“…First of all the rotational and translational dynamics of acetonitrile molecules in the neat AN as well as in various solvents have been studied using a wide kit of experimental techniques (FTIR, Raman, NMR relaxations, etc, see [8,[10][11][12] and the references therein). These data are very useful for comparative and metrological purposes.…”
Section: Resultsmentioning
confidence: 99%
“…Secondary band structures, noted and considered in some earlier studies [9,11,13], are observed at the present instrumental setting as well. Asymmetric shoulders are attributed in some works to the "hot bands" [13], whereas in others [8,10] those extra bands are believed to originate from intermolecular effects (aggregation of AN or H-bonding with solvent molecules). Without getting deep into polemic at the present stage of work, i. e. before starting on AN dynamics in IL environment, it is only important to note that the half-widths and the values of τ vib and τ rot (2) obtained by digital processing of ν2 and ν4 band profiles pertain well to the data available in literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation